Cost-effectiveness analysis of prognostic gene expression signature-based stratification of early breast cancer patients - Blank, Patricia R.; Filipits, Martin; Dubsky, Peter; Gutzwiller, Florian; Lux, Michael P.; Brase, Jan C.; Weber, Karsten E.; Rudas, Margaretha; Greil, Richard; Loibl, Sibylle; Szucs, Thomas D.; Kronenwett, Ralf; et al. (Pharmacoeconomics, 2015)
The individual risk of recurrence in hormone receptor-positive primary breast cancer patients determines whether adjuvant endocrine therapy should be combined with chemotherapy. Clinicopathological parameters and molecular tests such as EndoPredict(®) (EPclin) can support decision making in patients with estrogen receptor-positive, human epidermal growth factor receptor 2 (HER2)-negative cancer.Using a life-long Markov state transition model, we determined the health economic impact and incremental cost effectiveness of EPclin-based risk stratification in combination with clinical guidelines [German-S3, National Comprehensive Cancer Center Network (NCCN), and St. Gallen] to decide on chemotherapy use.Information on overall and metastasis-free survival came from Austrian Breast & Colorectal Cancer Study Group clinical trials 6/8 (n = 1,619) and published literature. Effectiveness was assessed as quality-adjusted life-years (QALYs). Costs (2010) were assessed from a German third-party payer perspective.Lifetime costs per patient ranged from <euro>28,268 (St.Gallen and EPclin) to <euro>33,756 (NCCN). Due to an imperfect prognostic value and differences in chemotherapy use, strategies achieved between 13.165 QALYs (NCCN) and 13.173 QALYs (EPclin alone) per patient. Using German-S3 as reference, three strategies showed dominant results (St. Gallen and EPclin, German-S3 and EPclin, EPclin alone). Compared to German-S3, the addition of EPclin saved <euro>3,388 and gained 0.002 QALYs per patient. Combining guidelines with EPclin remained preferable in sensitivity analysis.Our study suggests that molecular markers can be sensibly combined with clinical guidelines to determine the risk profile of adjuvant breast cancer patients. Compared with the current German best practice (German-S3), combinations of EPclin with the St. Gallen, German-S3 or NCCN guideline and EPclin alone were dominant from the perspective of the German healthcare system.
EVALuna2:17636